Edukasi dan Upaya Preventif Bahaya Pencemaran Logam Berat pada Makanan untuk Kesehatan Anak-Anak di Desa Gintung Kabupaten Pemalang - Izza Ratna Kumala (Lembaga Pengembangan Kinerja Dosen, 2024)
Heavy metals are chemical elements that can be toxic even at low concentrations. The presence of non-essential heavy metals in the environment can contaminate soil, water, and air. The consequences of this contamination affect the living organisms in the surrounding area. For instance, heavy metals in soil and water can contaminate plants growing in the region, which may then be processed as daily food sources, potentially impacting the health of those who consume them. Heavy metals such as lead (Pb), cadmium (Cd), mercury (Hg), and arsenic (As) are non-essential heavy metals that are of primary concern due to their toxic nature. The presence of heavy metals in food can hinder the growth and development of children, making it crucial to implement educational initiatives and preventive measures to reduce heavy metal contamination in daily consumed foods. This activity involves educating people about the dangers of heavy metal contamination in food and the actions that can be taken to reduce the concentration of heavy metals in the food we consume.